Software Patenting: Legal Standards in Europe and the US in view of Strategic Limitations of the IP Systems - Laub, Christoph (The Journal of world intellectual property, 2006)
The legal requirements concerning the statutory extent of protection for patent rights vary considerably throughout various global legal systems. Until today no harmonisation of US and the European provisions for the patentability‐assessment of Computer Implemented Inventions (CII) could be achieved. For more than 20 years an ever‐increasing field of intellectual creations has opened up for Patent protection by the US case law in force. According to the interpretation of the European Patent Convention (EPC), however, patents must be granted solely for technical inventions. A direct comparison of the two underlying International Property (IP) systems is therefore difficult to achieve and the granted legal titles must be carefully analysed when comparatively assessing their quality and economic exploitability. In this paper an initial concordance of European and US primary and secondary patent law is developed. Consequently the impact on “Software Patent” examination standards as applied by the legal executive authorities – European Patent Office (EPO) and United States Patent and Trademark Office (USPTO) – is determined. The detailed knowledge of the respective standards for so‐called statutory subject matter makes up the basis for a conclusive empirical study of granted and refused European CII patents and patent applications.